Modelling determinants of geographical patterns in the marital statuses of women in Nigeria (2021)
Marriage is an important social, cultural, and biological aspect of human life but is often affected by societal changes leading to differences in family formation and reproductive behaviour. Changes in marital patterns are component of transformations in a society’s social structure. Variations in marriage patterns exist within and across countries and over time. We examine the trends and spatial patterns of marital statuses among women of reproductive age (15–49 years) in Nigeria and further determine the associated factors based on the country’s north–south divide. Data were sourced from the Nigeria demographic and health survey conducted in 2003, 2008, 2013, and 2018, and the marital patterns were classified into four categories: never married, married, cohabiting, and formerly married. A Bayesian multinomial spatial model that simultaneously estimates parameters of different forms through a geo-additive predictor was adopted, and inference was based on Markov chain Monte Carlo. Findings reveal a north–south divide in marriage patterns. Women in the northern part of the country have a higher likelihood of being in marital union, while those in the south have a higher likelihood of cohabitation. A somewhat east– west divide was obtained for formerly married. Religion and ethnicity were found to be the major factors that account for differences in marital patterns across the divide and based on rural and urban residency. Cultural practices dictated by these variables would, therefore, continue to shape marital patterns and, by extension, fertility in Nigeria. The factors are hence important to be considered in marriage related policy formulation.